How Civil Institutions Build Resilience Organizational Practices Derived from Academic Literature and Case Studies - Langeland, Krista S. (RAND Corporation, 2016)
In an effort to support U.S. Air Force space community resilience objectives, researchers conducted a review of the academic literature defining and describing resiliency in various domains, and case-study reports about how organizations build resilient missions. This report summarizes key findings from this review that have broad application to organizations seeking to enhance resilience, which includes the space community.